2022
DOI: 10.1021/acs.est.2c06091
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid Insecticides and Their Metabolites Can Pass through the Human Placenta Unimpeded

Abstract: Studies on neonicotinoid (NEO) exposure in pregnant women and fetuses are scarce, and transplacental transfer of these insecticides is unknown. In this study, parent NEOs (p-NEOs) and their metabolites (m-NEOs) were determined in 95 paired maternal (MS) and cord serum (CS) samples collected in southern China. Imidacloprid was the predominant p-NEO in both CS and MS samples, found at median concentrations of 1.84 and 0.79 ng/mL, respectively, whereas N-desmethylacetamiprid was the most abundant m-NEO in CS (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Previous studies have reported high concentrations of ACE in various foods . Moreover, NEOs can be transferred from the mother to the fetus via the placenta; therefore, placental transmission may represent an internal exposure source of ACE in infants.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have reported high concentrations of ACE in various foods . Moreover, NEOs can be transferred from the mother to the fetus via the placenta; therefore, placental transmission may represent an internal exposure source of ACE in infants.…”
Section: Resultsmentioning
confidence: 98%
“…The occurrence of imidacloprid and acetamiprid and their metabolites has been demonstrated in paired urine and blood samples [ 53 ] as well as in paired urine and house dust [ 54 ]. Interestingly, NNIs can pass through the human placenta [ 16 ]. Although the Environmental Protection Agency (EPA) classifies these NNI insecticides as II (moderate) and III (slight) class toxic agents [ 55 ], our results suggest they could pose a real risk for the development of the human nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence points to a meaningful association between exposure to NNIs and mental diseases in rural populations [ 14 , 15 ]. Given their penetrability across the placenta [ 16 ] and blood-brain barrier [ 17 ], NNIs are likely to alter neurodevelopment in humans [ 18 , 19 ]. NNI-induced toxicity has already been probed in rodent neurons.…”
Section: Introductionmentioning
confidence: 99%
“…China is one of the largest producers and exporters of NEOs globally, with IMI production reaching 2.3 million tons in 2016. , As a consequence of the widespread application of NEOs in agricultural production, they are found in foods, in environmental samples, and even in human tissues. A recent study reported that NEO metabolites (m-NEOs) may increase the prevalence of liver cancer . NEOs and their metabolites can pass through the human placenta and may accumulate in the fetus . In vivo studies have found that some NEOs affect mammalian reproductive health, from decreased sperm quality in males and infertility in females as well as increased embryonic lethality and preterm birth. …”
Section: Introductionmentioning
confidence: 99%
“…9 NEOs and their metabolites can pass through the human placenta and may accumulate in the fetus. 10 In vivo studies have found that some NEOs affect mammalian reproductive health, from decreased sperm quality in males and infertility in females as well as increased embryonic lethality and preterm birth. 11−13 Following ingestion or inhalation pathways of exposure to NEOs, these compounds are metabolized by Phase I and Phase II pathways (Figure 1), which result in conjugation in human bodies.…”
Section: ■ Introductionmentioning
confidence: 99%